Adolescents and the system that judges them. Aspects and reasons which the law does not explain (Revista de Investigaciones Universidad del Quindío, 2021)
In this article reflect on the evolution of the adolescents judging system in Mexico and its relationship with the human development theory in order to know what is being referred to when talking about adolescents subject to the criminal justice system. A characteristic of the principle of specialization which is not described in the law.
Keywords: Development; criminal justice system